Acoustic and psychoacoustic analysis of the noise produced by the police force firearms - Guida, Heraldo Lorena [UNESP]; Diniz, Thiago Hernandes; Kinoshita, Sérgio Koodi [UNESP] (FapUNIFESP (SciELO), 2011)
Police officers are exposed to impact noise coming from firearms, which may cause irreversible injuries to the hearing system. Aim: To evaluate the noise exposure in shooting stands during gunfire exercises, to analyze the acoustic impact of the noise produced by the firearms and to associate it with tonal audiometry results. Study design: Cross-sectional. Materials and methods: To measure noise intensity we used a digital sound level meter, and the acoustic analysis was carried out by means of the oscillations and cochlear response curves provided by the praat software. 30 police officers were selected (27 males and 3 females). Results: The peak level measured was 113.1 dB(C) from a.40 pistol and 116.8 dB(C) for a.38 revolver. The values obtained for oscillation and praat was 17.9±0.3 Barks, corresponding to the rate of 4,120 and 4,580 Hz. Audiometry indicated greater hearing loss at 4,000Hz in 86.7% of the cases. Conclusion: With the acoustic analysis it was possible to show cause and effect between the main areas of energy excitation of the cochlea (praat cochlear response curve) and the frequencies of low hearing acuity.
Keywords: Firearms; Noise; Occupational; Police